Association of perchlorate, thiocyanate, and nitrate with dyslexic risk. (June 2023) - Zhu, Kaiheng; Wan, Yanjian; Zhu, Bing; Wang, Haoxue; Liu, Qi; Xie, Xinyan; Jiang, Qi; Feng, Yanan; Xiao, Pei; Xiang, Zhen; Song, Ranran
Abstract: Perchlorate, thiocyanate, and nitrate are sodium iodide symporter (NIS) inhibitors that disturb iodide uptake into the thyroid and have been implicated in child development. However, no data are available on the association between exposure to/related with them and dyslexia. Here, we examined the association of exposure to/related with the three NIS inhibitors with the risk of dyslexia in a case-control study. The three chemicals were detected in urine samples of 355 children with dyslexia and 390 children without dyslexia from three cities in China. The adjusted odds ratios for dyslexia were examined using logistic regression models. The detection frequencies of all the targeted compounds were 100%. After adjusting for multiple covariates, urinary thiocyanate was significantly associated with the risk of dyslexia ( P -trend = 0.02). Compared with the lowest quartile, children within the highest quartile had a 2.66-fold risk of dyslexia (95% confidence interval: 1.32, 5.36]. Stratified analyses showed that the association between urinary thiocyanate level and the risk of dyslexia was more pronounced among boys, children with fixed reading time, and those without maternal depression or anxiety during pregnancy. Urinary perchlorate and nitrate levels were not associated with the risk of dyslexia. This study suggests the possible neurotoxicity of thiocyanate or its parent compounds in dyslexia. Further investigation is warranted to confirm our findings and clarify the potential mechanisms. Graphical abstract: Image 1 Highlights: First data on the association of perchlorate, thiocyanate, and nitrate with dyslexia in children. Children were extensively exposed to the three chemicals in China. Urinary concentrations of thiocyanate may be related to dyslexia among children in China.